CTIM-17. EO2401 THERAPEUTIC VACCINE FOR PATIENTS WITH RECURRENT GLIOBLASTOMA: PHASE 1/2 ROSALIE STUDY (NCT04116658). (14th November 2022) - Reardon, David A; Idbaih, Ahmed; Vieito, Maria; Tabatabai, Ghazaleh; Stradella, Agostina; Ghiringhelli, François; Burger, Michael C; Mildenberger, Iris; González, Macarena; Hervieu, Alice; Martin, Marta Gil; Renovanz, Mirjam; et al.
Abstract: EO2401 includes microbial-derived, synthetically produced HLA-A2 restricted peptides with molecular mimicry to antigens (IL13Rα2, BIRC5 and FOXM1) upregulated in glioblastoma, and the CD4 helper peptide UCP2. Patients with glioblastoma at first progression received EO2401 (300µg/peptide, q2weeks x4 then q4weeks), EO2401+nivolumab (3mg/kg q2weeks), or E02401+nivolumab+bevacizumab (10mg/kg q2weeks). Cohort-1 included EO2401x2 then EO2401+nivolumab. EO2401+nivolumab was evaluated in Cohort-2a, as adjuvant treatment in Cohort-2b, and as neoadjuvant/adjuvant treatment in Cohort-2c. Cohort-3 assessed EO2401+nivolumab+bevacizumab. Part 1 included 40 patients (Cohort-1/3, Cohort-2a/23, Cohort-2b/3, Cohort-3/11). Part 2 allowed low-dose-bevacizumab (5mg/kg q2weeks) for symptomatic edema and enrolled 38 patients (Cohort-1/18, Cohort-2a/15, Cohort-2b/3; and recruiting Cohort-2c/2 target 6, Cohort-3/0 target 15).Safety assessment of part 1 showed EO2401+nivolumab+/-bevacizumab to be well tolerated with EO2401 associated toxicity limited to local administration site reactions (48%; all grade 1-2). The nivolumab-/bevacizumab-toxicity was consistent with historical single-agent data. Strong CD8 T cell ELISPOT responses against the 3 vaccine peptides and cross-reactivity against targeted antigens was demonstrated in the majority of evaluable patients. Immune response was confirmed with tetramer staining of specific CD8 either ex vivo or after in vitro stimulation. For part 1, median progression-free survival (mPFS), and median survival (mOS) for EO2401+nivolumab (Cohorts-1/2/2b, n=29 median follow-up [mFU] 14.0 months) were 1.8 and 10.6 months. Patients on EO2401+nivolumab+bevacizumab (n = 11 mFU 9.6 m) had mPFS 5.5 months and 9 patients alive 7-12.4 months. Objective Response Rate/Disease Control Rate for EO2401+nivolumab and EO2401+nivolumab+bevacizumab was 10%/34% and 55%/82%.Median treatment duration for Cohort-2a part 1 was 6.1 weeks (1/23 on treatment), while it was 10.0 weeks (8/15 on treatment) for Cohort-2a part 2. Overall, in part 2, 36% received low-dose-bevacizumab.EO2401 generated strong immune responses and was well tolerated. Addition of standard bevacizumab to EO2401+nivolumab improved PFS and tumor response. Symptom driven low-dose-bevacizumab supported longer treatment durations. Outcome of study part 2 will be presented.